The global business environment : challenges and responsibilities. - Morrison, Janet (Houndmills: Palgrave Macmillan, 2016)
Offering an accessible introduction to the business environment, this edition of Janet Morrison's textbook explores the economic, political, social, legal, cultural and technological dimensions that affect businesses..
includes references and index.
Keywords: International business enterprises; International economic relations; International trade; Competition, International; Globalization -- Economic aspects